Efectos de una cobertura viva de Teramnus labialis (L.F.) Sprengel sobre las arvenses en campos citricolas - Gutierrez Rojas, I.R.=700 1 Felipe Lopez, M. de los A.; Perez Carmenate, R.; Fontes, D.; Daniel, Vernont I, D.
(Es, En)
Ilus., 18 ref.
Keywords: MALEZAS; TERAMNUS; LEUGMINOSAS FORRAJERAS; COBERTURA VERDE; CUBA; TERAMNUS LABIALIS